Short Cationic Peptidomimetic Antimicrobials - Rajesh Kuppusamy; Mark Willcox; David StC. Black; Naresh Kumar (MDPI AG, 2019)
The rapid growth of antimicrobial resistance against several frontline antibiotics has encouraged scientists worldwide to develop new alternatives with unique mechanisms of action. Antimicrobial peptides (AMPs) have attracted considerable interest due to their rapid killing and broad-spectrum activity. Peptidomimetics overcome some of the obstacles of AMPs such as high cost of synthesis, short half-life in vivo due to their susceptibility to proteolytic degradation, and issues with toxicity. This review will examine the development of short cationic peptidomimetics as antimicrobials.